Visão do profissionais da estratégia saúde da família sobre comportamento autolesivo em adolescetes - Ferreira, Solange Oliveira (2024)
INTRODUCTION: Self-injurious behavior is considered a multifactorial, complex and growing problem in Brazil. The general population practices self-injury, but it is in adolescence that there is greater recurrence, and among adolescents, girls are the ones who practice it the most. Although the Family Health Strategy (Estratégia Saúde da Família - ESF) is one of the gateways and organizers of health services in the Unified Health System (Sistema Único de Saúde - SUS), professionals still find it difficult to understand and manage adolescents with self-injury properly and safely. The guiding question of this research is to find out how ESF professionals view self-injurious behavior among adolescents. GENERAL OBJECTIVE: To find out ESF professionals' views on mental health care in relation to self-injurious behavior among adolescents. SPECIFIC OBJECTIVES: To identify how ESF professionals understand the causes of self-injurious behavior among adolescents; To identify the care offered by ESF professionals in the mental health of adolescents with issues related to self-injury; To describe the types of articulation and actions with the social assistance network to monitor adolescents with issues related to self-injury. METHODOLOGY: The universe of the research was made up of nine higher education and technical professionals from two ESFs in a city in the Cariri region of Ceará. The data was collected through recorded interviews which were transcribed and analyzed using the critical dialectical theoretical framework and thematic analysis. RESULTS AND DISCUSSION: The research revealed important aspects such as the difficulty in identifying whether or not adolescents are at risk of death. They also understand that adolescents with self-injurious behavior reveal intense psychological pain and that their main stressors and triggers are family conflict, poverty, inappropriate use of the internet, lack of cultural and sports facilities in the community where they live and exposure to alcohol and other drugs. Professionals' management is still based on complaints and medication with antidepressants. They believe that PHC can help these adolescents, but only if psychologists and psychiatrists are part of the team. FINAL CONSIDERATIONS: The professionals have little experience of caring for adolescents with self-injurious behavior, they don't demonstrate in their work process that the expanded clinic is effective, with little mention of matrix support in primary care. They mention some points in the Health Care Network (RAS) and the social assistance network, but have difficulty understanding what each service offers. They recognize that self-injury in adolescents is a result of psychological and sociodemographic factors; however, they do not hold shared discussions among the team to understand the context in which self-injury occurs.